Hair coat characteristics and sweating rate of Braford cows in Brazil - Abaker Bertipaglia, Elaine Cristina; da Silva, Roberto Gomes; Cardoso, Vania; Fries, Luis Alberto (Elsevier B.V., 2007)
This paper deals with the effects of hair coat characteristics on the sweating rate of Brazilian Braford cows and estimation of heritabilities and genetic correlations of these traits. Data (n=1607) on hair length, coat thickness, hair diameter, number of hairs per unit area, coat reflectance and sweating rate were recorded from heifers and cows of a commercial herd managed on range under extensive system. The data were analyzed considering the following effects on the model for hair coat traits: classes of sires and contemporary groups; linear effects of month and genotype; linear and quadratic effects of age. The effect of sire was important (P<0.05) for all hair coat traits, except for number of hairs; contemporary groups affected (P<0.05) all hair coat traits; the effect of sampling month was important (P<0.05) for hair length and reflectance; genotype affected (P<0.05) hair length, diameter and coat reflectance; the quadratic effect of age was important (P<0.05) only for coat reflectance. Two models were used to analyze the sweating rate. The first model considered the following fixed effects: classes of contemporary groups and sires; linear effect of genotype, coat thickness, hair length, hair diameter, number of hairs, coat reflectance; linear and quadratic effects of time of day, age, air temperature, partial vapour pressure and radiant heat load. The second model used for the sweating rate considered the same fixed effects for the first model, except that the hair coat characteristics were adjusted for important effects used in the models to analyze hair coat traits. All meteorological factors and contemporary groups were important (P<0.05) on variation of sweating rate in both models. The Restricted Maximum. Likelihood (REML) method was used to estimate variance and covariance components under the sire model. Results included heritability estimates in narrow (h(2)) and broad (H) sense for single-trait analyzes: hair thickness (h(2)=0.16; H-2=0.26); hair length (h(2)=0.18; H-2=0.39); number of hairs (h(2)=0.08 +/- 0.07; H-2=0.08 +/- 0.07); hair diameter (h(2)=0.12 +/- 0.07; H-2=0.12 +/- 0.07); coat reflectance (h(2)=0.30; H-2=0.42); and sweating rate (h(2)=0.10 +/- 0.07; H-2=0.10 +/- 0.07). In general, the genetic correlations between the adaptive traits were favorable as for the direction to select for adaptation in tropical environment; however, they presented high standard errors. The results of this study imply that hair coat characteristics and sweating ability are important for the adaptability to heat stress and they must be better studied and further considered for selection for genetic progress of adaptation in tropical environment. (C) 2007 Elsevier B.V All rights reserved.
Keywords: adaptation; beef cattle; genetic parameters; hair coat; sweating rate